How will Atlantic coral reefs look in the future? Predicted shift in the distribution of key species of shallow reef environments in face of climate change - Souza, Silas Candido Principe de (2023)
Climate change is leading to shifts in the distribution of species. Whether species range contract or expand, this will cause the reshuffling of assemblages, with potential negative consequences on the functioning of ecosystems. Within the marine realm, coral reefs are among the most threatened ecosystems due to climate change and other Anthropogenic activities. Thus, understanding how the distribution of key species of coral reefs may change in the future is of paramount necessity. Early prediction of range shifts can drive the management strategy and enable mitigation or conservation actions. In this work we used species distribution models to predict the potential shifts in the distribution of important species among four major groups: reef builders, herbivorous invertebrates, macroalgae and reef fish. In general, our results revealed that major changes are expected in the distribution of species on the Tropical Western Atlantic, with many species expanding poleward and losing suitable areas in their current distribution. However, patterns varied among species and groups, with some species expanding, others contracting and some keeping stable distributions. In the final part of the work, we aggregated the results of multiple distribution models to identify how climate change may impact the richness and composition of Atlantic reefs. Again, despite some consistent general trends (richness decrease in areas of high diversity), there is some variability among groups. Together, our results reinforce that Atlantic reefs may look very different in the future with less functional diversity and that there is an urgent need to attain with the goals of the Paris agreement in order to ensure an at least better scenario for the Western Atlantic coral reefs.